2016
DOI: 10.5617/adno.2554
|View full text |Cite
|
Sign up to set email alerts
|

Differensiert undervisning for høytpresterende elever med stort læringspotensial

Abstract: Tilpasset opplæring er et sentralt prinsipp i norsk skole og innebærer at alle elever har krav på differensiert undervisning. Samtidig er differensiering utfordrende å ivareta både for erfarne og mindre erfarne lærere. I denne artikkelen argumenterer vi for at det er viktig at lærerutdannere gir studentene både undervisning og veiledet trening om differensiering. I studien har vi bedt lærerstudenter ta utgangspunkt i elever de har hatt i sin 12-ukers praksis i ungdomsskolen eller videregående skole, og som de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…with higher learning potential in contemporary education (Renzulli, 2012;NMER, 2016;Winstanley, 2016). Either way, if student teachers find the notion of enacting such differentiation challenging, then teacher education needs to address this issue (Brevik & Gunnulfsen, 2016;Darling-Hammond, 2010;Grossman, 2005). Given student teachers' lack of experience, teacher education has much to offer to create a safe learning environment for these students.…”
Section: Environment Differentiation?mentioning
confidence: 99%
See 1 more Smart Citation
“…with higher learning potential in contemporary education (Renzulli, 2012;NMER, 2016;Winstanley, 2016). Either way, if student teachers find the notion of enacting such differentiation challenging, then teacher education needs to address this issue (Brevik & Gunnulfsen, 2016;Darling-Hammond, 2010;Grossman, 2005). Given student teachers' lack of experience, teacher education has much to offer to create a safe learning environment for these students.…”
Section: Environment Differentiation?mentioning
confidence: 99%
“…Although differentiation is essential for all learners, studies have shown that schools have inadequate knowledge about students with higher learning potential, and that instruction is differentiated only to a small extent to meet these students' needs and abilities (Norwegian Ministry of Education and Research [NMER], 2016). This situation may be explained by the fact that these students receive little attention in teacher education (Brevik & Gunnulfsen, 2016), and one could argue, more broadly in education in general.…”
Section: Introductionmentioning
confidence: 99%
“…Norskspråklig forskningslitteratur gir god støtte med tanke på identifisering av elever med stort laeringspotensial (Smedsrud & Skogen, 2016;Lie, 2014;Skogen & Idsøe, 2011) og tematiserer tilpasset opplaering og differensiert undervisning både generelt og i enkeltfag (Knutsen & Emstad, 2021;Brevik & Gunnulfsen, 2016;Ramton et al, 2021;Smedsrud, 2018;Smedsrud, 2014;. Forskere har sett naermere på elevenes egne erfaringer (Lenvik et al, 2021;Smedsrud, 2018), og på laererstudenters og laereres perspektiv Brevik & Gunnulfsen, 2016). Studentene mener det er viktig, men utfordrende å gi tilpasset opplaering til elevgruppen.…”
Section: Innledningunclassified
“…Gifted students are not considered to have special needs; however, they require differentiation. Pre-service teachers have described gifted students as diverse and have reported difficulties in developing and implementing differentiated teaching targeting this student group [33].…”
Section: The Norwegian Contextmentioning
confidence: 99%